Oceanic redox evolution in an early Cambrian intrashelf basin, South China - Yuyue Han; Meng Cheng; Jianbo Chen; Thomas J. Algeo; Bo Ran; Mengchun Cao; Zihu Zhang; Haiyang Wang; Dasheng Zhao; Tao Dong; Feng Wang; Taiping Huang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A lyophilized CHA–lateral flow platform for point-of-care detection of miR-106b-5p from L1CAM-Immunocaptured small extracellular vesicles in Alzheimer's disease - Ran Xu; Hao Chen; Chao Zhao; Xiqing Ding (Analytica Chimica Acta, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Up-scaling of radon migration in rock media based on multi-resolution CT pore modeling and volume averaging method - Yuan-Chao Chen; Dong Xie; Zhong-Luo Liao; Jun Zeng; Qian-Ran Jia (Journal of Environmental Radioactivity, 2026)

Hydrocarbon charging dynamics and its coupling with reservoir densification in a tight sandstone system: Insights from the Jurassic of the Yangxia Sag, Kuqa Depression - Chang-chao Chen; Jun Li; Jinz-hou Wang; Ling Li; Hao-ran Gao; Zheng-lian Pang; Xiu-yan Chen; Min Yang (Applied Geophysics, 2026)

Carbon and phosphorus regeneration during organic matter decomposition in aquatic ecosystems: characteristics, mechanisms, and environmental effects - Chao Yin; Yan Zeng; Jingan Chen; Peng Liao; Jia Yu; Guangrong Ran; Baohua Xiao; Xudong Guo; Ziyan Zhang; Jingfu Wang; Haiquan Yang; Quan Yuan (Geochimica et Cosmochimica Acta, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

Relationships between sludge metabolic activity and the degree of extracellular polymeric substance stripping - Xianbao Wang; Xiyu Liu; Jiarong Ran; Baisha Song; Jinlei Cheng; Tiantian Chen; Anlong Zhang; Chao Zhu; Pengkang Jin (ENGINEERING Environment, 2026)

Trans-cinnamaldehyde alleviates high-fat diet-induced oxidative stress in zebrafish via direct and gut microbial mediated activations of antioxidant pathways - Delong Meng; Xiaoying Zhu; Jingyu Luan; Xingyu Chen; Tsegay Teame; Benjamin Earl Niemann; Chao Ran; Yalin Yang; Qianwen Ding; Yuanyuan Yao; Zhen Zhang; Zhigang Zhou (Marine Life Science & Technology, 2026)

LC-HRMS profiling of processing-induced formation of carcinogenic N-nitrosamines in Areca nut products - Yuan-Jhe Chang; Hsueh-Ju Lu; Yet-Ran Chen; Yi-Jhen Wang; Rajendra Bose Muthukumaran; Chiung-Wen Hu; Mu-Rong Chao (Food Chemistry, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

An improved ion-exchange-to-silver-salt procedure for δ18O measurement of nitrate in natural samples - Bo Wang; Chao Li; Ying Wang; Linbao Chen; Yuting Wang; Ran Ma; Zhengyu Zhu; Youping Zhou (Analytica Chimica Acta, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Moderate-intensity aerobic exercise inhibits cell pyroptosis to improve myocardial ischemia-reperfusion injury - Yu Wang; Yushan Li; Chaofan Chen; Hailong Zhang; Weili Liu; Chao Wu; Haonan Chen; Ran Li; Jinghan Wang; Yingchao Shi; Shengfang Wang; Chuanyu Gao (Molecular Biology Reports, 2025)

Assessment of flood risk in jinsha river basin based on land use value and PSR model - Xiao Chen; Ran Zhai; Wen Fang; Liwen Xu; Lili Liang; Juanru Yang; Hanlin Man; Zhenyu Lv; Chao Wang; Deng Liu; Mengqing Cui (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Recovery of siliceous ecosystems promoted Early Silurian climatic cooling - Huan Xu; Bo Ran; Terry T. Isson; Xinyang Chen; Chao Luo; Yi Li; Yiqing Zhu; Tong Sun; Yuyue Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Biochar and iron minerals facilitate the reduction of pollution and sequestration of carbon in chloramphenicol-contaminated soil under dry conditions - Pengfei Cheng; Junliang Chen; Ran Xu; Qin Tian; Xiaobo Luo; Zhicong Dai; Zhiliang Li; Yao Lu; Lianghui Li; Kuan Cheng; Chao Guo; Guanlin Li; et al. (Applied Soil Ecology, 2025)

Cyanobacterial dominance under CO2(aq)-limited conditions increases ecological risks in karst reservoirs - Guangrong Ran; Jingan Chen; Ziyan Zhang; Yan Zeng; Chao Yin; Jia Yu; Dong Wu; Haijun Yuan; Moshan Cen (Water Research, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Preliminary study on ameliorative effects of P-Hydroxycinnamic acid on high-fat diet-induced injury in zebrafish - Qianyao Kuang; Delong Meng; Zhen Zhang; Xingyu Chen; Tsegay Teame; Hongwei Yang; Yalin Yang; Chao Ran; Yuanyou Li; Zhigang Zhou (Fish & Shellfish Immunology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Novel carbonylomics with stable isotope-coded derivatization for non-targeted analysis of reactive carbonyl species in cooking oils - Chiung-Wen Hu; Yuan-Jhe Chang; Yi-Jhen Wang; Yet-Ran Chen; Marcus S. Cooke; Mu-Rong Chao (Journal of Hazardous Materials, 2025)

TdCCA with Dual-Modal Signal Fusion: Degenerated Occipital and Frontal Connectivity of Adult Moyamoya Disease for Early Identification - Yuchen Ran; Yingwei Fan; Shuang Wu; Chao Chen; Yangxi Li; Tianxin Gao; Houdi Zhang; Cong Han; Xiaoying Tang (Translational Stroke Research, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

Whey protein-structured oleogels: Effect of α-lactalbumin addition and ultrasonication treatment on oleogelation - Qiu-Ya Ji; Ran Feng; Yu-Nong Chen; Chao Zhang; Jiao Wu; Meng-Jie Yu; Bao Zhang (Food Chemistry, 2025)

Novel angiotensin-I-converting enzyme (ACE) inhibitory peptides from Porphyra haitanensis: Screening, digestion stability, and mechanistic insights - Xianjiang Ye; Ran Yang; Zhizhi Yang; Baote Huang; Talha Riaz; Chao Zhao; Jicheng Chen (Food Bioscience, 2025)

Numerical simulation study on the radon exhalation mechanism of building walls influenced by coupled heat-moisture-air transfer - Yuan-Chao Chen; Dong Xie; Qian-Ran Jia; Jun Zeng; Guo-Jie Chen; Yang Yang (Journal of Environmental Radioactivity, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Effects of plant aromas on stress recovery and brain activity in university students - Nan Zhang; Chao Liu; Yuying Ren; Wenxuan Li; Ran Chen; Weijun Gao (Building and Environment, 2025)

Predicting Persistent Aneurysm Filling After Pipeline Embolization Device Treatment in Patients with Intracranial Aneurysm: Development and External Validation of a Nomogram Model - Linggen Dong; Chao Wang; Xiheng Chen; Mingtao Li; Tong Li; He Liu; Yang Zhao; Ran Duan; Weitao Jin; Yukun Zhang; Yang Wang; Ming Lv (Translational Stroke Research, 2025)

Quantitatively tracing the decomposition of endogenous particulate organic carbon during sinking in (sub-)deep reservoirs: Using radiocarbon isotopes Δ14C - Chao Yin; Yan Zeng; Jingan Chen; Guangrong Ran; Haiquan Yang; Jia Yu; Jingfu Wang; Ziyan Zhang; Xudong Guo (Water Research, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Land use patterns change N and P cycling bacterial diversity in an acidic karst soil - Zhou Li; Wangfei Qin; Yongliang You; Jihui Chen; Xuechun Zhao; Rui Dong; Xinyao Gu; Song Cui; Chao Chen; Erinne Stirling; Ran Xue (Agriculture, Ecosystems & Environment, 2025)

Effect of Bacillus velezensis T23 solid-state fermentation product on growth, gut and liver health, and gut microbiota of common carp (Cyprinus carpio) - Xingyu Chen; Shubin Liu; Tsegay Teame; Jia Luo; Yao Liu; Qingwen Zhou; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Zhen Zhang; Zhigang Zhou (Aquaculture, 2025)

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Effect of crowding stress on liver health, gut permeability and gut microbiota of genetically improved farmed tilapia (GIFT, Oreochromis niloticus) - Jian Zhang; Jie Chen; Hui Liang; Ming Li; Wenhao Zhou; Yalin Yang; Zhen Zhang; Qianwen Ding; Chao Ran; Zhigang Zhou (Aquaculture, 2025)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

Cost-Effective multifunctional bilayer structural hydrogel evaporator for stable solar desalination and wastewater treatment - Xin-Yu Zhou; Shu-Chao Song; Wen-Xiu Wang; Hui-Ran Jin; Shan Yun; Ai-Bin Huang; Jing Chen (Chemical Engineering Journal, 2024)

Cu/Fe3O4 magnetic aerogel for the capture and immobilization of iodine anion from water - Xin-Yu Zhou; Kai-Wei Chen; Ao-Tian Gu; Hui-Ran Jin; Wei-Jie Sun; Shu-Chao Song; Shan Yun; Ping Mao; Yi Yang; Jing Chen (Journal of Cleaner Production, 2024)

Fabrication of zein/modified cyclodextrin nanofibers for the stability enhancement and delivery of curcumin - Yao Hu; Nicholas H. Rees; Chao Qiu; Jinpeng Wang; Zhengyu Jin; Ran Wang; Yinhua Zhu; Han Chen; Pengjie Wang; Siyuan Liu; Fazheng Ren; Gareth R. Williams (Food Hydrocolloids, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Pichia pastoris composition expressed aerolysin mutant of Aeromonas veronii as an oral vaccine evaluated in zebrafish (Danio rerio) - Yuan-Yuan Yao; Qing-Shuang Zhang; Shu-Bin Liu; Hong-Wei Yang; Xing-Yu Chen; Ya-Lin Yang; Chen-Chen Gao; Chao Ran; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Marine Life Science & Technology, 2024)
Vaccines are one of the most practical means to stop the spreading of Aeromonas veronii in aquaculture. In this study, virulence factor aerolysin mutant NTaer which has lost its hemolytic activity was used as a target antigen. Pichia pastoris constitutive secretory expression NTaer (GS115-NTaer) was used as a potential safe oral vaccine to evaluate its effectiveness on zebrafish immunity. The result shows that vaccination of GS115- NTaer for four weeks did not affect the growth performance of the host, while eliciting an effective immune protective response. Compared with the control group, the GS115-NTaer could significantly up-regulate the relative expression level of the intestinal tight junction protein 1α ( TJP1α ) gene, and significantly increased the contents of lysozyme (LYZ), complement C3 and C4 in the gut, indicating that the innate immune response of the fish was activated. The relative gene expression levels of macrophage-expressed gene 1 ( MPEG1 ) and T cell receptor ( TCR-α ) in the gut, and MPEG1 , CD4 , CD8 , TCR-α , GATA3, and T-bet in the spleen were all increased significantly, indicating that the cellular immune response of the fish was activated. Furthermore, the contents of serum IgM and intestinal mucosa IgZ antibodies were significantly increased, which showed that humoral immunity was also activated. Moreover, inoculation with GS115-NTaer significantly changed the structure of gut microbiota. In particular, the relative ratio of (Firmicutes + Fusobacteriota + Bacteroidota)/Proteobacteria was significantly higher than that of the control and GS115 groups. Lastly, the vaccinated fish were challenged with A. veronii, and the relative percent survival of GS115 and the GS115-NTear groups was 14.28% and 33.43%. This improvement of immunity was not only due to the specific immune response but also attributed to the improvement of innate immunity and the gut microbiota which was demonstrated by the germ-free zebrafish model. Collectively, this study provides information on the effectiveness of GS115-NTear as an oral vaccine for the green prevention and control of A. veronii infection in fish aquaculture.

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

Mechanism and ecological environmental risk assessment of peroxymonosulfate for the treatment of heavy metals in soil - Lai-Min Zhang; Lu-Lu Long; Qi-Ran Zhu; Chao Chen; Min Xu; Jun Wu; Gang Yang (Science of The Total Environment, 2024)

Experimental and theoretical study on seismic behavior of a new UHPFRC sandwich wall and wall-wall joint - Ru-Rui Liu; Ran Ding; Yong-Tao Sun; Jian-Sheng Fan; Ding-Qiu Chen; Jian-Chao Xu (Engineering Structures, 2024)

Gut bacterial community and gene expression alterations induced by transgenic Bt maize contribute to insecticidal activity against Mythimna separata - Chao Xu; Junyu Luo; Li Wang; Xiangzhen Zhu; Hui Xue; Ningbo Huangfu; Xueke Gao; Dongyang Li; Kaixin Zhang; Ran Chen; Jichao Ji; Changying Niu; et al. (Journal of Pest Science, 2024)

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Key design and layout factors influencing performance of three-way catalytic converters: Experimental and semidecoupled numerical study under real-life driving conditions - Banglin Deng; Zetao Chen; Chengqi Sun; Shoujun Zhang; Weijiao Yu; Min Huang; Kaihong Hou; Jiaqi Ran; Lili Zhou; Chao Chen; Xinxiang Pan (Journal of Cleaner Production, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

The effect of stabilized culture of Lactobacillus rhamnosus GCC-3 on gut and liver health, and anti-viral immunity of zebrafish - Hui Liang; Yadong Xie; Ming Li; Jie Chen; Wenhao Zhou; Rui Xia; Qianwen Ding; Yuanyuan Yao; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Fish & Shellfish Immunology, 2023)

Quantifying the contribution of temperature, salinity, and climate change to sea level rise in the Pacific Ocean: 2005-2019 - Junlin Ran; Nengfang Chao; Lianzhe Yue; Gang Chen; Zhengtao Wang; Tangting Wu; Chengchun Li (Frontiers in Marine Science, 2023)
In recent decades, Pacific Ocean’s steric sea level anomaly (SSLA) has shown prominent patterns among global sea level variations. With ongoing global warming, the frequency and intensity of climate and sea level changes have increased, particularly in the tropical Pacific region. Therefore, it is crucial to comprehend the overall trends and mechanisms governing volumetric sea level changes in the Pacific. To accurately quantify the spatiotemporal evolution characteristics of density-driven sea level change in the Pacific Ocean (PO) from 2005 to 2019, we decomposed temperature and salinity into linear trends, interannual variations, seasonal variations, and residual terms using the STL (seasonal-trend decomposition based on loess) method. To evaluate the influence of ocean temperature, salinity, and climate change on density-driven sea level change and its underlying mechanisms, we decompose temperature as well as salinity changes through into the Heaving (vertical displacements of isopycnal surfaces) and Spicing (density-compensated temperature and salinity change) modes. The findings reveal an average steric sea level rise rate of 0.34 ± 0.16 mm/yr in the PO from 2005 to 2019. Thermosteric sea-level accounts for 82% of this rise, primarily due to seawater temperature rise at depths of 0-700 m caused by Heaving mode changes. Accelerated SSLA increase via the thermosteric effect has been connected to interactions between greater Ekman downwelling from surface winds, radiation forcing linked to global greenhouse gases, and changes in the Pacific warm currents triggered by El Niño-Southern Oscillation (ENSO) episodes. Although salinity is affected by the Subantarctic Mode Water (SAMW) and the Antarctic Intermediate Water (AAIW) in the southern Indian Ocean, however the significance of salinity in sea level change is little compared to the role played by thermocline shift. This study offers a substantial contribution to the field, providing robust data and technical support, and facilitating a deeper understanding of the mechanisms underlying the effects of temperature and salinity on sea level changes during periods of rapid climate change, thus enhancing the accuracy of future predictions regarding sea level rise.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Chemical decontamination of foods using non-thermal plasma-activated water - Samuel Herianto; Rachelle D. Arcega; Chih-Yao Hou; How-Ran Chao; Ching-Chang Lee; Chia-Min Lin; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Dietary supplementation of yeast mannan enhances antiviral immunity of zebrafish (Danio rerio) - Hui Liang; Yadong Xie; Yu Li; Mingxu Xie; Ming Li; Wei Zhou; Jie Chen; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Aquaculture, 2023)

Nucleic acid adductomics – The next generation of adductomics towards assessing environmental health risks - Marcus S. Cooke; Yuan-Jhe Chang; Yet-Ran Chen; Chiung-Wen Hu; Mu-Rong Chao (Science of The Total Environment, 2023)

Botrytis cinerea BcSSP2 protein is a late infection phase, cytotoxic effector - Wenjun Zhu; Mengxue Yu; Ran Xu; Kai Bi; Shuang Yu; Chao Xiong; Zhiguo Liu; Amir Sharon; Daohong Jiang; Mingde Wu; Qiongnan Gu; Ling Gong; et al. (Environmental Microbiology, 2022)
Summary Botrytis cinerea is a broad‐host‐range necrotrophic phytopathogen responsible for serious diseases in leading crops. To facilitate infection, B . cinerea secretes a large number of effectors that induce plant cell death. In screening secretome data of B . cinerea during infection stage, we identified a phytotoxic protein (BcSSP2) that can also induce immune resistance in plants. BcSSP2 is a small, cysteine‐rich protein without any known domains. Transient expression of BcSSP2 in leaves caused chlorosis that intensifies with time and eventually leads to death. Point mutations in eight of 10 cysteine residues abolished phytotoxicity, but residual toxic activity remained after heating treatment, suggesting contribution of unknown epitopes to protein phytotoxicity. The expression of bcssp2 was low during the first 36 h after inoculation and increased sharply upon transition to late infection stage. Deletion of bcssp2 did not cause statistically significant changes in lesions size on bean and tobacco leaves. Further analyses indicated that the phytotoxicity of BcSSP2 is negatively regulated by the receptor‐like kinases BAK1 and SOBIR1. Collectively, our findings show that BcSSP2 is an effector protein that toxifies the host cells, but is also recognized by the plant immune system.

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Exogenous artificial DNA forms chromatin structure with active transcription in yeast - Jianting Zhou; Chao Zhang; Ran Wei; Mingzhe Han; Songduo Wang; Kaiguang Yang; Lihua Zhang; Weigang Chen; Mingzhang Wen; Cheng Li; Wei Tao; Ying-Jin Yuan (Science China Life Sciences, 2022)
Yeast artificial chromosomes (YACs) are important tools for sequencing, gene cloning, and transferring large quantities of genetic information. However, the structure and activity of YAC chromatin, as well as the unintended impacts of introducing foreign DNA sequences on DNA-associated biochemical events, have not been widely explored. Here, we showed that abundant genetic elements like TATA box and transcription factor-binding motifs occurred unintentionally in a previously reported data-carrying chromosome (dChr). In addition, we used state-of-the-art sequencing technologies to comprehensively profile the genetic, epigenetic, transcriptional, and proteomic characteristics of the exogenous dChr. We found that the data-carrying DNA formed active chromatin with high chromatin accessibility and H3K4 tri-methylation levels. The dChr also displayed highly pervasive transcriptional ability and transcribed hundreds of noncoding RNAs. The results demonstrated that exogenous artificial chromosomes formed chromatin structures and did not remain as naked or loose plasmids. A better understanding of the YAC chromatin nature will improve our ability to design better data-storage chromosomes.

Seepage field distribution and water inflow laws of tunnels in water-rich regions - Zheng Li; Zi-quan Chen; Chuan He; Chun-chi Ma; Chao-ran Duan (Journal of Mountain Science, 2022)

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

Study on the correlation of bisphenol A exposure, pro-inflammatory gene expression, and C-reactive protein with potential cardiovascular disease symptoms in young adults - Chao-Ming Tsen; Jia-Hong Liu; Da-Peng Yang; How-Ran Chao; Jyh-Larng Chen; Wei-Chun Chou; Yi-Chen Ho; Chun-Yu Chuang (Environmental Science and Pollution Research, 2021)

Multipath mitigation in GNSS precise point positioning based on trend-surface analysis and multipath hemispherical map - Ran Lu; Wen Chen; Danan Dong; Zhiren Wang; Chenglong Zhang; Yu Peng; Chao Yu (GPS Solutions, 2021)

Evaluation of the stability of vegetated slopes according to layout and temporal changes - Yun-peng Li; Chao Hu; Li Jian; Ran Zhao; Chen Li (Journal of Mountain Science, 2021)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

Medial Preoptic Area Modulates Courtship Ultrasonic Vocalization in Adult Male Mice - Shu-Chen Gao; Yi-Chao Wei; Shao-Ran Wang; Xiao-Hong Xu (Neuroscience Bulletin, 2019)

Levels of PCDD/Fs, PBDEs, and PBDD/Fs in Breast Milk from Southern Taiwan - Men-Wen Chen; Bryan Angelo A. Castillo; Din-Yan Lin; How-Ran Chao; Lemmuel L. Tayo; Yan-You Gou; Fu-An Chen; Kuo-Lin Huang (Bulletin of Environmental Contamination and Toxicology, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

MicroRNA-99a regulates early chondrogenic differentiation of rat mesenchymal stem cells by targeting the BMPR2 gene - Xiaozhong Zhou; Jing Wang; Hongtao Sun; Yong Qi; Wangyang Xu; Dixin Luo; Xunjie Jin; Chao Li; Weijian Chen; Zhousheng Lin; Feimeng Li; Ran Zhang; et al. (Cell and Tissue Research, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Wild soybean roots depend on specific transcription factors and oxidation reduction related genesin response to alkaline stress - Huizi DuanMu; Yang Wang; Xi Bai; Shufei Cheng; Michael K. Deyholos; Gane Ka-Shu Wong; Dan Li; Dan Zhu; Ran Li; Yang Yu; Lei Cao; Chao Chen; et al. (Functional & Integrative Genomics, 2015)

Kinematic single-frequency relative positioning for LEO formation flying mission - Pei Chen; Leizheng Shu; Ran Ding; Chao Han (GPS Solutions, 2015)

Knockdown of response gene to complement 32 (RGC32) induces apoptosis and inhibits cell growth, migration, and invasion in human lung cancer cells - Ran Xu; Chao Shang; Jungang Zhao; Yun Han; Jun Liu; Kuanbing Chen; Wenjun Shi (Molecular and Cellular Biochemistry, 2014)

Subaquatic volcanic eruptions in continental facies and their influence on high quality source rocks shown by the volcanic rocks of a faulted depression in Northeast China - XuanLong Shan; JiYan Li; ShuMin Chen; QingChang Ran; GuiBiao Chen; Chao Liu (Science China Earth Sciences, 2013)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Polybrominated diphenyl ethers in background surface soils from the Yangtze River Delta (YRD), China: occurrence, sources, and inventory - Yan-Ping Duan; Xiang-Zhou Meng; Chao Yang; Zhao-Yu Pan; Ling Chen; Ran Yu; Feng-Ting Li (Environmental Science and Pollution Research, 2010)

MicroRNA-128 inhibits glioma cells proliferation by targeting transcription factor E2F3a - Yu Zhang; Tengfei Chao; Ran Li; Wei Liu; Yang Chen; Xingqi Yan; Yanhua Gong; Bin Yin; Wei Liu; Boqing Qiang; Jizhong Zhao; Jiangang Yuan; et al. (Journal of Molecular Medicine, 2009)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)